2005
DOI: 10.1051/0004-6361:20041608
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR observations of NGC 6822: AGB stars, distance, metallicity and structure

Abstract: Abstract.Observations in the IJK s wave bands covering the central 20 × 20 of the Local Group galaxy NGC 6822 have been made with the William Herschel Telescope in La Palma. They have allowed us to characterize, for the first time in the near-infrared across the whole galaxy, its late-type stellar population (i.e. red giant and asymptotic giant branch stars) and to derive from the ratio between carbon-rich and oxygen-rich asymptotic giant branch stars an indication about spatial variations in metallicity. Thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 50 publications
10
89
0
Order By: Relevance
“…All selected targets are brighter than 17.45 mag in K 0 and have (J − K) 0 > 0.74 mag, although redder stars were targeted preferentially. Cioni & Habing (2005) detected the RGB tip (TRGB) at K s = 17.10 ± 0.01 mag, while Sibbons et al (2010) report that it varies across the galaxy by ΔK = 1.36 mag, with an average value of K = 17.48 ± 0.26 mag. Davidge (2003) adopted a distance modulus of 23.49 mag based on the Cepheid and RGB tip measurements of Gallart et al (1996b), and measured the onset of the RGB tip in K band near K = 17 mag.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…All selected targets are brighter than 17.45 mag in K 0 and have (J − K) 0 > 0.74 mag, although redder stars were targeted preferentially. Cioni & Habing (2005) detected the RGB tip (TRGB) at K s = 17.10 ± 0.01 mag, while Sibbons et al (2010) report that it varies across the galaxy by ΔK = 1.36 mag, with an average value of K = 17.48 ± 0.26 mag. Davidge (2003) adopted a distance modulus of 23.49 mag based on the Cepheid and RGB tip measurements of Gallart et al (1996b), and measured the onset of the RGB tip in K band near K = 17 mag.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Lee et al (1993) and Salaris & Cassisi (1998) gave (m − M) 0 = 23.46 ± 0.08 and 23.71 ± 0.14 using the RGB tip brightness as a distance indicator; Gallart et al (1996) estimate (m − M) 0 = 23.49 ± 0.08 using UBVRI photometry of eight Cepheids; Cioni & Habing (2005) using near-infrared (NIR) photometry of AGB stars found (m − M) 0 = 23.34 ± 0.12; Gieren et al (2006) found (m − M) 0 = 23.312 ± 0.021 through NIR photometry of Cepheids in the innermost region of NGC 6822. More recently, significant differences among the distance estimates to NGC 6822, based on the use of the classical Cepheid period-luminosity relation, have been extensively investigated by Feast et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this dredge-up, AGB evolution can be classified according to atmospheric abundance, i.e., starting with oxygen-rich (C/O < 1) M-giant stars that evolve into carbon-rich (C/O > 1) C stars (Nowotny et al 2001). These two types of AGB stars can be used to estimate the metallicity of the parent galaxy because the ratio of C stars to M-giants (C/M) is anti-correlated with the metal abundance (Battinelli & Demers 2005;Cioni & Habing 2005;Cioni 2009). The AGB stars are among the brightest and coolest stars of the intermediate-age stellar population; accordingly, they appear mostly in near-infrared color−magnitude diagrams (CMDs).…”
Section: Introductionmentioning
confidence: 99%